Reservoir heterogeneity of the Longmaxi Formation and its significance for shale gas enrichment. Issue 12 (15th September 2020) - Zhang, Qin; Feng, Liang; Pang, Zhenglian; Liang, Pingping; Guo, Wei; Zhou, Shangwen; Guo, Wei; Lu, Bin
Abstract: To better determine the sweet spot in the vertical profile of the Longmaxi Formation, the shale heterogeneity was systematically investigated. A series of experiments were conducted on 40 shale samples collected from the Lower Silurian Longmaxi Formation in the Weiyuan shale gas field. The results indicated that total organic carbon (TOC), the mineral composition, methane adsorption capacity, and porosity of the four sub‐layers in the Longmaxi shale varied significantly. In terms of the TOC, the mid‐lower Long11 1 had the highest value, followed by Long11 3, while the TOC values of Long11 2 and Long11 4 were quite low. As for mineral composition, the mid‐lower Long11 1 had the highest quartz content, Long11 2 and Long11 3 had equivalent quartz, carbonate, and clay mineral contents, and Long11 4 had higher clay mineral and carbonate contents, but a lower quartz content. Shale porosity and methane adsorption capacity were the highest in the mid‐lower Long11 1, followed by Long11 3, Long11 2, Long11 4, and the upper Long11 1 . The micro‐heterogeneity represented by the fractal dimension ranged from 2.590 to 2.750, with an average of 2.670. The mid‐lower Long11 1 had the largest fractal dimension, followed by Long11 3, Long11 2, Long11 4, and the upper part of Long11 1 had the smallest fractal dimension. The sedimentary environment controls the macro‐heterogeneity in the vertical profile. The micro‐heterogeneity depends on diagenesis, which can be investigated by the different effects of minerals on micropore development. The strong micro‐heterogeneity results in better preservation conditions for shale gas. The mid‐lower Long11 1 was rich in gas generation material (TOC) with enough storage space and is characterized by good preservation conditions, leading to the highest gas content of the four sub‐layers. In addition, the high brittle mineral content is conducive to fracturing and the formation of a fracture network. Thus, the middle ‐Long11 1 is the "sweet spot" in the vertical profile for the shale gas development. Abstract : Longmaxi formation is heterogeneous both in macro‐scale and micro‐scale. The mid‐lower Long11 1 was rich in gas generation material (TOC) with enough storage space (large BET and porosity) and is characterized by good preservation conditions (large fractional dimension), leading to the highest gas content of the four sub‐layers.